A STUDY OF AWARENESS AND USE OF E-RESOURCES AMONG USERS OF DEGREE COLLEGE LIBRARIES - Shantaram, Pranesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Electronic publishing has led to new era of communication and information sharing. It creates opportunities for users as well as authors and publishers. In this study the awareness and use of e-resources is tested the level of satisfaction and what extend they use the e-resources. The study also that the problem face by the users.